Effects of weight cutting on exercise performance in combat athletes: A meta-analysis - Brechney, G. C.; Cannon, J.; Goodman, S. P. (International Journal of Sports Physiology and Performance, 2022)
Weight cutting in combat sports is a prevalent practice whereby athletes voluntarily dehydrate themselves via various methods to induce rapid weight loss (RWL) to qualify for a lower weight category than that of their usual training body weight. The intention behind this practice is to regain the lost body mass and compete at a heavier mass than permitted by the designated weight category. The purpose of this study was to quantitatively synthesize the available evidence examining the effects of weight cutting on exercise performance in combat-sport athletes. Following a systematic search of the literature, meta-analyses were performed to compare maximal strength, maximal power, anaerobic capacity, and/or repeated high-intensity-effort performance before rapid weight loss (pre-RWL), immediately following RWL (post-RWL), and 3 to 36 hours after RWL following recovery and rapid weight gain (post-RWG). Overall, exercise performance was unchanged between pre-RWL and post-RWG (g = 0.22; 95% CI, -0.18 to 0.62). Between pre-RWL and post-RWL analyses revealed small reductions in maximal strength and repeated high-intensity-effort performance (g = -0.29; 95% CI, -0.54 to -0.03 and g = -0.37; 95% CI, -0.59 to -0.16, respectively; both P = .03). Qualitative analysis indicates that maximal strength and power remained comparable between post-RWL and post-RWG. These data suggest that weight cutting in combat-sport athletes does not alter short-duration, repeated high-intensity-effort performance; however, there is evidence to suggest that select exercise performance outcomes may decline as a product of RWL. It remainsunclear whether these are restored by RWG.